Protective effect of Naringin on experimental hindlimb ischemia/reperfusion injury in rats. (1st November 2016) - Gürsul, Cebrail; Ekinci Akdemir, Fazile Nur; Akkoyun, Turan; Can, İsmail; Gül, Mustafa; Gülçin, İlhami
Abstract: This study was designed to investigate the antioxidant effects of Naringin, in ischemia/reperfusion (I/R)-induced skeletal muscle injury in rats. The rats were randomly allocated into three groups including control, I/R and I/R + Naringin groups. Muscle tissues of I/R groups revealed significantly higher antioxidant enzyme activities, and increased levels of malondialdehyde, as specific a marker of the lipid peroxidation and tissue damage, compared to the control group ( p  < 0.05). Levels of these parameters in muscle revealed significant reductions in the I/R + Naringin group compared to the I/R group ( p  < 0.05). Histopathological examination of ischemia muscles in the I/R group showed significant degeneration and inflammation compared to the control group, whereas ischemic muscles of Naringin-administered group showed significant reduction in degeneration and inflammation compared to the I/R group ( p  < 0.05). We suggest that the protective effect of Naringin may reduce the I/R injury in cases of extremity injuries with acute vascular complications, extremity surgery with prolonged tourniquet application.